COVID-19 impact on the health and emotional well-being of the general population. (20th October 2021) - Cabrera-Léon, A; Sánchez-Cantalejo, C; Rueda, MM; Saez, M; Enrique, I; Ferri, R; Castro, L; Barceló, MA; Villegas, R; Daponte, A
Abstract: : A tremendous number of studies describe results on the evolution of the COVID-19 impact on infected patients, hospital admissions, deaths, mental health and well-being of the population. However, there are hardly any reports on its impact and evolution since the beginning of the pandemic with clinical, contextual and individual perception information. Our work describes the research project called Health Care and Social Survey (ESSOC, Encuesta Sanitaria y SOCial). It arises from the need to provide specific, reliable, early, and timely data on the impact of COVID-19 that can be considered when making decisions to prepare and provide an effective Public Health response in the different affected populations. It is linked to official statistical operations included in the Andalusian Regional Government and has also been granted a favorable opinion by the Research Ethics Committee. The ESSOC is based on a Real-World Data design. It integrates observational data extracted from multiple sources including information based on surveys and clinical, epidemiological, population, and environmental registries. The surveys have an overlapping panel design with a total of over 22, 000 effective interviews being carried out over three years from the beginning of the state of alarm in Spain. Their geographical scope is the Autonomous Region of Andalusia (8.4MM people, the fifth most populated region in Europe), and the population scopes are general population, population residing in disadvantaged areas, and population over the age of 55. The conceptual approach of this study encompasses all aspects affecting health that will contribute to an extraordinary increase in the current knowledge of the impact of the COVID-19 pandemic. Its results will be very useful for cross-disciplinary comparisons in population-based studies, and the methodology developed will serve as a model to be applied in other epidemiological studies. Key messages: It is needed to provide specific, reliable, early, and timely data on the impact of COVID-19 that can be considered when making decisions to prepare and provide an effective Public Health response. Our research project integrates observational data extracted from multiple sources including information based on surveys and clinical, epidemiological, population, and environmental registries.